2006
DOI: 10.1002/pmic.200600033
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic characterization of acid stress response inSynechocystis sp. PCC 6803

Abstract: A comparative proteomic analysis using 2-DE coupled with MALDI-MS and LC-MS/MS was performed in Synechocystis sp. PCC 6803 to identify protein candidates involved in acid stress response in cyanobacteria. Comparison of soluble proteins from the cytoplasmic fraction of cells grown on media set at pH 7.5 and 5.5 using 2-DE identified four proteins, which showed significant changes in the abundance. Surprisingly, several general stress proteins, either the heat shock family proteins or chaperonins, did not show p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 48 publications
5
50
0
Order By: Relevance
“…This complements earlier findings concerning acid-stress response, which revealed several mechanisms enabling various microorganisms to survive under low pH in laboratory conditions (Kallas & Castenholz, 1982;Foster & Hall, 1991;Huang et al, 2002;Kurian et al, 2006). Among them are analyses of Synechocystis 6308, a strain isolated from Lake Wisconsin, which turned out to be able to respond to and survive the acid stress by increasing the pH in culture (Huang et al, 2002).…”
Section: Discussionsupporting
confidence: 71%
“…This complements earlier findings concerning acid-stress response, which revealed several mechanisms enabling various microorganisms to survive under low pH in laboratory conditions (Kallas & Castenholz, 1982;Foster & Hall, 1991;Huang et al, 2002;Kurian et al, 2006). Among them are analyses of Synechocystis 6308, a strain isolated from Lake Wisconsin, which turned out to be able to respond to and survive the acid stress by increasing the pH in culture (Huang et al, 2002).…”
Section: Discussionsupporting
confidence: 71%
“…The positive effect of increasing pH on the proteolytic activity of HhoA correlated well with the pH tolerance of Synechocystis sp. strain PCC 6803 cells, which are able to survive under slightly acidic conditions but prefer alkaline conditions for growth, and thus with the pH experienced in the periplasm (24). In contrast, A. thaliana Deg1 was most active at a low pH, pH 6.0, and the activity decreased at a higher pH, which corresponds to the conditions prevalent in the thylakoid lumen (6).…”
Section: Discussionmentioning
confidence: 92%
“…A previous proteomic analysis using Synechocystis sp. strain PCC 6803 showed that its OxdC homolog was induced and secreted into the periplasm when cells were grown under acidic conditions (20). The mechanisms linking induction of OxdC to growth under low-pH conditions are not yet clear but likely involve YvrL.…”
Section: Discussionmentioning
confidence: 99%